2017
DOI: 10.3892/mmr.2017.6100
|View full text |Cite
|
Sign up to set email alerts
|

A novel pathway in NSCLC cells: miR-191, targeting NFIA, is induced by chronic hypoxia, and promotes cell proliferation and migration

Abstract: MicroRNAs (miRs) have emerged as being important in cancer biology. miR‑191 is a conserved miRNA, which has been investigated in detail and is reported to be induced by hypoxia-inducible factor (HIF)‑1α and has an contributory action in the progression of breast, hepatic and pancreatic cancer. However, the effects of miR‑191 in the progression of lung cancer are a subject of debate. In the present study, it was found that the expression of miR-191 was significantly upregulated in non‑small cell lung cancer (NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“… 13 , 14 , 15 , 16 , 17 Previous studies have reported that miR-34a, miR-502 and miR-22 play the role as tumor suppressors in breast cancer, 18 , 19 , 20 but miR-32 and miR-191 function as oncogenes in breast cancer and lung cancer. 21 , 22 miR-140 appeared to be positively controlled by retinoblastoma and to antagonize the effect of Rb depletion on spherogenesis and tumorigenesis, 23 and it can regulate the cell invasion of esophageal cancer via controlling Slug expression. 24 However, the correlation of miR-140 expression with invasion and angiogenesis in breast cancer has not been reported.…”
Section: Introductionmentioning
confidence: 96%
“… 13 , 14 , 15 , 16 , 17 Previous studies have reported that miR-34a, miR-502 and miR-22 play the role as tumor suppressors in breast cancer, 18 , 19 , 20 but miR-32 and miR-191 function as oncogenes in breast cancer and lung cancer. 21 , 22 miR-140 appeared to be positively controlled by retinoblastoma and to antagonize the effect of Rb depletion on spherogenesis and tumorigenesis, 23 and it can regulate the cell invasion of esophageal cancer via controlling Slug expression. 24 However, the correlation of miR-140 expression with invasion and angiogenesis in breast cancer has not been reported.…”
Section: Introductionmentioning
confidence: 96%
“…In these samples, NFIB was down-regulated as a result of tumour specific expression of miR-212 and miR-92b [90]. These findings suggest that microRNA dysregulation may be a common pathway resulting in NFI down-regulation in [28,90,153,[202][203][204], the importance of NFI as a target in vivo remains to be determined.…”
Section: Regulatory Mechanisms Governing Nfi Expressionmentioning
confidence: 85%
“…NSCLC accounts for 75-85% of lung cancer cases (2,3). Compared with SCLC, NSCLC cells grow and divide more rapidly, resulting in diffusion and metastasis at an earlier stage of disease (4). However, only 15% of patients with NSCLC are diagnosed at an early stage of the disease and current treatment modalities, including surgical resection and chemoradiation are inadequate (5).…”
Section: Introductionmentioning
confidence: 99%